Tris (2-aminoethyl) Amine Functionalized Nanoporous Silica SBA-15 as a Potential Drug Carrier for Citalopram - Fatemeh Dalayi (International Journal of Basic Science in Medicine, 2019)
Introduction: Ordered nanoporous silica such as SBA-15 has a great potential for application in controlled drug release systems. Chemical modification of the silanol groups of SBA-15 allows better control over drug loading and release. Therefore, tris(2-aminoethyl) amine-functionalized mesoporous silica SBA-15 was evaluated as a potential carrier for the delivery of citalopram. Methods: Tris (2-aminoethyl) amine-functionalized SBA-15 was synthesized and characterized by various methods. Citalopram was loaded on the functionalized SBA-15 and drug release into simulated body fluid (SBF) solution and phosphate buffers was investigated. Results: The optimal condition for loading of the citalopram was obtained at pH = 9 after stirring for 5 minutes. The release profile of citalopram was monitored in phosphate buffers with three different pH values of 5, 7, and 8. A faster release rate at lower pH value was observed, suggesting a weaker interaction because of the protonation of the amino group of the functionalized SBA15. The average release rate of citalopram from each gram of functionalized SBA-15 was 12 µg h-1 in the SBF. Conclusion: The results showed that loading amount and release rate of citalopram depended on pH value and the release process showed a very slow release pattern. Therefore, tris (2-aminoethyl) amine-functionalized SBA-15 is a suitable carrier for controlled release of citalopram and has a great potential for disease therapy.